2014
DOI: 10.1088/2053-1591/1/4/045102
|View full text |Cite
|
Sign up to set email alerts
|

Water soluble and metal-containing electron beam resist poly(sodium 4-styrenesulfonate)

Abstract: Popular electron beam resists such as PMMA, ZEP and HSQ all use solvent or base solutions for processing, which may attack the sub-layers or substrate that are made out of organic semiconducting materials. In this study we show that water soluble poly(sodium 4-styrenesulfonate), or sodium PSS, can be used as a negative electron beam resist developed in water. Moreover, since PSS contains metal sodium, its dry etching resistance is much higher than PMMA. It is notable that sodium PSS's sensitivity and contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In 1993, the IBM T.J. Watson Research Center group reported both the resist material synthesis and corresponding patterning technique. Two decades later, Abbas et al reported a peculiar utilization of polystyrene sulfonate as a negative tone resist with remarkable lift-off capability [156] . We should also mention water-soluble negative tone resists based on fullerenes.…”
Section: Non-bio-derived Resistsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1993, the IBM T.J. Watson Research Center group reported both the resist material synthesis and corresponding patterning technique. Two decades later, Abbas et al reported a peculiar utilization of polystyrene sulfonate as a negative tone resist with remarkable lift-off capability [156] . We should also mention water-soluble negative tone resists based on fullerenes.…”
Section: Non-bio-derived Resistsmentioning
confidence: 99%
“…Two decades later, Abbas et al reported a peculiar utilization of polystyrene sulfonate as a negative tone resist with remarkable lift-off capability. [156] We should also mention water-soluble negative tone resists based on fullerenes. [157] The authors showed high-resolution (30 nm) negative tone patterning with an acceptable sensitivity of 800 µC cm −2 , eliminating pre-exposure or postexposure treatments.…”
Section: Non-bio-derived Resistsmentioning
confidence: 99%
“…One example is poly(sodium 4-styrenesulfonate), which is a water soluble and developable negative tone resist containing the metal sodium. 4 A second example is organometallic metal carbonyl polymer, cyclopentadienylcarbonyldiphenylphosphinobutanoyliron, which contains metal iron. 5 Alternatively, metal Cr can be incorporated physically into polystyrene (PS) resist using cothermal evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…6 For negative resists, lift-off is rarely used for pattern transfer because a slightly positively tapered profile, instead of an undercut profile, would usually result because of electron forward scattering. Nevertheless, lift-off using the negative resist such as polystyrene 7 or water soluble poly(sodium 4-styrenesulfonate) 8 can be realized when using very low energy exposure such that the resist bottom is inadequately exposed and thus dissolves fast in the developer. It is important to point out that, for lifting off some structures such as nanoscale trenches or holes, a negative resist is preferred as it offers far less exposure time than positive resists (yet a complicated double lift-off process using a positive resist can be employed to obtain such structures 9 ).…”
Section: Introductionmentioning
confidence: 99%